A Study of Cost Effectiveness of Artemisinine Combination Therapy (Act) Among Paediatric Patients at a Tertiary Medical Centre in South West Nigeria (Global Journal of Medical Research, 2012)
This retrospective study was to compare the cost effectiveness of oral ACT as a first line of treatment of malaria with non-oral ACTs in paediatric patients aged 5 years and below. The study was carried out at Children Outpatients Clinic of Federal Medical Centre, Abeokuta Ogun State in Nigeria between April and September 2005. Clinical case notes of paediatric patients aged 5 years and below were used. Three hundred and fifty (350) patients were randomly selected with only 328 patients meeting the inclusion criteria. The number consisted of 153 (46.6%) males and 175 (53.4%) females. The mean age of patients was 2.3 years (SD 1.4). Oral Chloroquine/Sulphadoxine and Pyrimethamine (CQ/SP) was administered to 127 (38.7%) patients, 113 (34.5%) patients had Quinine/Sulphadoxine and Pyrimethamine (QSP) while 88 (26.8% ) patients had Arthemisine/ Sulphadoxine, Pyrimethamine (ASP). The cure rate for CQ/SP, Quinine/SP and Arthemisine/SP were (11.0%), (22.1%) and (97.7%) respectively. It was only Artemisinine/SP that met the 7.5% efficacy rate recommended by WHO. Data on the therapeutic efficacy of the treatment given to the patients were collected and analyzed using descriptive statistics of frequency distribution and percentages with statistical package Microsoft SPSS 10.0 window version
Keywords: ACTs; Non ACTs; Chloroquine; Quinine; Sulphadoxine; Pyrimethamine